Legislative Functions of the House of Representatives in the Perspective of the 1945 Constitution of the Republic of Indonesia - Andrian Fernando; Tri Susilowati (Jurnal Indonesia Sosial Sains, 2023)
All the objectives of the State are specified in the constitution or essential law of the State as expressed in the Prelude to the 1945 Constitution of the Republic of Indonesia (1945 Constitution), which is contained in the fourth passage which states: 1) safeguard the whole Indonesian country and Indonesia's slaughter; 2) advance public government assistance; 3) teach the existence of the country; and 4) take part in completing world request. In particular, in the 1945 Constitution, the scope and definition of the law are not very clear. Article 20 of the 1945 Constitution only mentions the authority of the DPR to make laws by mutual agreement with the government. Article 24 C paragraph (1) only stipulates that the Constitutional Court has the authority to review laws against the constitution. The lack of clarity over the legislative function of the DPR, causes the State to need to make a standard rule regarding the Law on Procedures and Mechanisms for Forming Legislation. In Indonesia, there have been several regulations regarding arrangements for the Formation of laws and regulations, namely TAP MPRS Number XX/MPRS/1966 concerning Sources of Orderly Law, TAP MPR Number III/MPR/2000 and enhanced by Law Number 10 of 2004 concerning Formation of Legislation. Feeling that the previous regulations were incomplete, on 12 August 2011, the government enacted Law Number 12 of 2011 amendment of Law Number 10 of 2004 concerning the Formation of Legislation.